SPECIFICITY OF ANTHROPONYMS IN RUSSIAN AND ENGLISH - Mullajonova, Zukhroyulduz Alimzhonovna (Oriental Journal of Education, 2026)
Anthroponyms are an important part of the onomastic system (onomastics), which reflects the cultural experience of a people, their historical traditions, and their ideas about the individual, society, religion, gender, and social roles. The meaning of anthroponyms extends far beyond simply designating a person: a name is a symbolic phenomenon embodying the linguistic, cultural, cognitive, and social aspects of human existence. A name is also a tremendous asset, the most essential attribute of a person, the most vivid expression of their character, personality, and a vibrant connection between their integrity and their culture and tradition. In this article, we will attempt to compare the characteristics of proper names in Russian and English, identify their systemic similarities and differences, and examine the principles of their construction.